Comprehensive analysis of LAMC1 expression and prognostic value in kidney renal papillary cell carcinoma and clear cell carcinoma - Bai, Jianrong; Zheng, Axiu; Ha, Yanping; Xu, Xiaoqing; Yu, Yaping; Lu, Yanda; Zheng, Shaojiang; Shen, Zhihua; Luo, Botao; Jie, Wei (Frontiers in Molecular Biosciences, 2022)
Background: Laminin subunit gamma 1 (LAMC1) protein is associated with tumor cell invasion and metastasis. However, its role in kidney cancer remains unclear. In this work, we sought to probe the expression as well as its carcinogenic mechanisms of LAMC1 in kidney renal papillary cell carcinoma (KIRP) and kidney renal clear cell carcinoma (KIRC). Methods: Public databases including TIMER, Oncomine, UALCAN, TISIDB, TCGA, Kaplan–Meier plotter, UCSC Xena, cBioPortal, SurvivalMeth, KEGG, GeneMANIA, Metascape, GSCALite and GDSC were adopted, and the expression, clinical pathological correlation, prognostic signatures, dominant factors influencing LAMC1 expression, DNA methylation levels, gene mutations, copy number variations, functional networks, and drug sensitivity were analyzed. Expression of LAMC1 protein in clinical KIRP and KIRC was validated using tissue array. Results:LAMC1 expression in KIRP and KIRC were significantly higher than those in normal tissues. High LAMC1 expression indicated poor overall survival in KIRP patients and better overall survival in KIRC patients. Through the univariate and multivariate Cox analysis, we found that high LAMC1 expression was a potential independent marker for poor prognosis in KIRP, however it implied a better prognosis in KIRC by univariate Cox analysis. In addition, the LAMC1 expression in KIRP and KIRC was negatively correlated with methylation levels of LAMC1 DNA. Interestingly, LAMC1 expression was positively correlated with the infiltration of CD8+ T cells, dendritic cells and neutrophils in KIRP; however, it was positively correlated with the infiltration of CD4+ T cells, macrophages and neutrophils but negatively correlated with B cells in KIRC. Moreover, high level of CD8+ T cells is beneficial for KIRC prognosis but opposite for KIRP. LAMC1 may participate in signaling pathways involved in formation of adherens junction and basement membrane in KIRP and KIRC, and the high expression of LAMC1 is resistant to most drugs or small molecules of the Genomics of Drug Sensitivity in Cancer database. Conclusion: Enhanced LAMC1 expression suggests a poor prognosis in KIRP while a better prognosis in KIRC, and these opposite prognostic signatures of LAMC1 may be related to different immune microenvironments.